PEMANFAATAN SAGU LOKAL SEBAGAI BAHAN BAKU EDIBLE COATING DAN PENGARUHNYA TERHADAP MASA SIMPAN TOMAT - Novita Condro; Joice L. Tumiwang (AGRICOLA, 2016)
Edible coating has much developed and used in wide variety of fruits and vegetables to extend shelf life by retard the ripening, prevent enzymatic browning reactions or retention the freshness of flavor and aroma. Edible coating is one way to extend the shelf life of the product due to different permeability of CO2, O2, water evaporation fruit and vegetables coating so as to reduce the rate of metablism and loss of water. The aim of this study was to investigate the use of edible coating from local raw materials namely sago in order to extend the shelf life of tomatoes. Also is a local product that researchers consider it necessary to conduct research on the use edible coating made from sago starch locally for industrial of postharvest and locally farmers. From the results of this study showed that use of  edible coating in tomatoes affect the shel life tomatoes, where tomatoes coated have a shelf life much longer that 10 days compared to non coating which reached 8 days at the same temperature 28 0C and all treatment are likely to experience changes in the quality of physicochemical during storage and affect the shelf life of tomatoes.